2002
DOI: 10.1111/j.1749-6632.2002.tb03017.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐Seeking Behavior and Compliance of Diabetic Patients in a Rural Area of South India

Abstract: India, being a rural country, has unique problems regarding the treatment compliance of diabetic patients. This community‐based study was undertaken in a rural primary health center area near Chennai (Madras) in order to better understand treatment‐seeking behavior, compliance patterns, and reasons for noncompliance among rural diabetics. Compliance was indirectly measured through patient interviews and drug use charts. Of the 112 patients interviewed, 72% had some symptoms at the time of diagnosis, and the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 7 publications
0
17
1
Order By: Relevance
“…Similarly, a study done in rural south India reported that lack of family cooperation was one of the reasons for non adherence [12]. Hence, in addition to individual counseling, family counseling should also be an essential component in the care of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study done in rural south India reported that lack of family cooperation was one of the reasons for non adherence [12]. Hence, in addition to individual counseling, family counseling should also be an essential component in the care of DM.…”
Section: Discussionmentioning
confidence: 99%
“…Cooperation with social workers should be undertaken to assist with adequate support [30]. Further, it is of the utmost importance to assess patients’ use of herbal remedies, particularly if used as an alternative to allopathic medicine [28, 29], to avoid a switch between different caregivers that might interrupt compliance and glycaemic control, negatively affecting health [31]. Nurses need to elicit information about use from patients in a sensitive and non-judgemental manner, as many users believe that health care providers would admonish them for it and thus do not inform about the treatments used [28].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension was also very prevalent, which, in association with diabetes, increases the risk of complications and morbidity. [14]…”
Section: Discussionmentioning
confidence: 99%
“…[13] All patients with diabetes require access to education on how to manage the condition; medication, particularly for blood glucose and blood pressure lowering, frequent monitoring of blood glucose and blood pressure, regular monitoring of feet, eyes and kidneys function for potential complications, and access to care in order to both prevent and treat complications when they occur. [14] Compliance and adherence to medication is crucial in diabetics and poses a challenge to caregivers around the world. Factors shown to influence patient compliance include ease of access to facilities, cost of medication(s), patient's cultural or family factors, and patients’ perception and knowledge about their illness.…”
Section: Introductionmentioning
confidence: 99%